The Role of Affective Attitude as A Mediator Between Religiosity and Purchase Intention on Islamic Bank - Riptiono, Sulis (Universitas Ahmad Dahlan, 2021)
This research examines the affective attitude as a mediator between religiosity and consumer purchase intentions of Islamic bank products. This study was located in Kebumen using 100 people as a sample taken using the purposive sampling technique. The collected data were processed using SPSS and analyzed using path analysis with the Sobel test. The findings of this study indicate that significant and positive religiosity towards affective attitude and purchase intention and affective attitude is also proven to be critical factors in increasing purchase intention. In addition, this study also confirms that affective attitude is established as a mediating variable for the relationship between religiosity and consumer purchase intention of Islamic bank products.